2017
DOI: 10.15406/mojes.2017.02.00027
|View full text |Cite
|
Sign up to set email alerts
|

Diatom Diversity and Organic Matter Sources in Water Bodies around Chennai, Tamil Nadu, India

Abstract: In the present study, sediment samples were collected from different locations and diverse environments around Chennai city to evaluate the environmental conditions and the health of the water bodies. The grain size analysis of the sediment samples reveals that sand is the dominant fraction deposited in highenergy coastal environments followed by silty sand, sandy silt, while as the sediment samples of Cooum River and fresh water lakes and Buckingham canal show the dominance of silty clay and clayey silt respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This is in consistent to the case described by Abimbola et al (1999) where a ferruginous sandstone is the precursor material for a ferricrete. However, the higher values of SiO 2 in the meta-sandstone is due to the occurrence of quartz (Achyuthan 2004), whereas the lower values of silica in the ferricrete reflect the production of Secondary quartz through dissolution of original quartz grains (Bheemalingeswara et al 2013). Therefore, when compared to ferruginous sandstone or meta-sandstone in content of the major oxides, the ferricrete deposit has higher values of Fe 2 O 3 and lower values of SiO 2 and Al 2 O 3 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in consistent to the case described by Abimbola et al (1999) where a ferruginous sandstone is the precursor material for a ferricrete. However, the higher values of SiO 2 in the meta-sandstone is due to the occurrence of quartz (Achyuthan 2004), whereas the lower values of silica in the ferricrete reflect the production of Secondary quartz through dissolution of original quartz grains (Bheemalingeswara et al 2013). Therefore, when compared to ferruginous sandstone or meta-sandstone in content of the major oxides, the ferricrete deposit has higher values of Fe 2 O 3 and lower values of SiO 2 and Al 2 O 3 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, in some places, voids and fractures are filled by secondary quartz, suggesting variable environmental conditions within the ferricrete (Ramakrishnan and Tiwari 2006; Figure 6(C)). Achyuthan (2004) described the development of ferricretes found in different geological settings and reported that they consist of iron oxides and hydroxides (goethite), and quartz. We found a similar ferricrete deposit in our study area where finely crystalline hematite and goethite along with highly corroded quartz make up the matrix (Figure 5(A, B and D)).…”
Section: Discussionmentioning
confidence: 99%
“…Iron–duricrusts (ferricretes) have been used as morpho- and pedo-stratigraphic markers in landscape reconstruction (Bourman 2007) and as indicators of climatically controlled geomorphic and pedological processes (Achyuthan 2004). They have application in construction and industrial processes (McNally 2007; Ramanaidou and Morris 2010; Oyelami and Van Rooy 2016) and as raw materials for cement production (Emofurieta et al 1995; Gebresilassie et al 2012).…”
Section: Introductionmentioning
confidence: 99%